How the shopping cart explains global consumerism - Warnes, Andrew, 1974- (University of California Press, 2018)
"Picture a familiar scene: long lines of shoppers waiting to check out at the grocery store, carts filled to the brim with the week's food. While many might wonder what is in each cart, Andrew Warnes implores us to consider the symbolism of the cart itself. In his inventive new book, Warnes examines how the everyday shopping cart is connected to a complex web of of food production and consumption that has spread from the United States throughout the world. Today, shopping carts represent choice and individual autonomy for consumers, a recognizable American way of life that has become a global phenomenon. This succinct and and accessible book provides an excellent overview of consumerism and the globalization of American culture that is relevant to numerous fields of study"--Provided by publisher.